Pembangunan modul latihan pendidikan seksualiti untuk guru program Pendidikan Khas Integrasi (PPKI) peringkat Sekolah Rendah / Shariza Said - Shariza, Said (2017)
Previous research revealed pupils with learning disabilities (LD) portray sexual misconduct in schools.Teachers encountered difficulties in handling sexual behavior of pupils due to lack of exposure on sexual education and lack of good resources. This research was conducted with the aim of developing sexual education training modules for teachers from LD Integrated Special Education Program (PPKI) in primary schools. This module was developed with the aim of upgrading teachers knowledge and skills. This study applied design and developmental research in three phases. (1) Need Analysis Phase, (2) Design and Development Phase and (3) Implementation and Evaluation Phase. Survey by Questionnaires used in Need Analysis Phase involves 634 PPKI primary school teachers in Malaysia. Need Analysis determined the relevant training and input required.The level of knowledge and skills on sexual education was moderate among respondents in this study. These findings determined the required elements to be used in sexual education training modules in the Design and Development Phase. In the first round eight experts were interviewed using Fuzzy Delphi method. Findings from the interviews were used to develop questionnaire which was circulated to 42 experts from various agencies. Items with defuzzification value above 0.5, indicates acceptance of these items by experts. All items suggested by researcher was above 0.5 in defuzzification value. These items were incorporated in the module. There are seven sub modules with objective, content, delivery strategy, evaluation and resource materials. This module is named as Personal Life Management Module. It gives guidance on the application of sexual education in KSSR Life Management Field. This module is then evaluated by 12 experts to determine the validity of it‟s content. This module was assessed in Implementation and Evaluation Phase. This module was implemented on 31 PPKI teachers with teaching experience of five years and above on children with learning disabilities. Paired sample t- test was used to compare knowledge and skills in pretest and post-test. The level of knowledge indicates value of t(30) = 11.79, p<0.05 and level of skill with value t(30) = 11.25, p<0.05. A significant difference was established between pre-test and post-test in knowledge and skills. Knowledge and skills of teachers increased with the sexual education training. The efficiency level of the module was high with an overall min of 4.50 and standard deviation of 0.57. Interview with five respondents show that they are satisfied with the module as the module was able to enhance their knowledge and skills in sexuality education. Positive results on LD pupil‟s sexuality knowledge were obtained following the use of the module by three PPKI teachers. In conclusion, this research has produced sexuality education training module with high usability. This module has the potential in training and introducing sexuality education to PPKI teachers